Pengaruh Sikap dan Motivasi Konsumen terhadap Minat Beli pada UMKM Warung Sembako Rasqya di Kelurahan Sambinae Kota Bima - Anfani Anfani; Ita Purnama; Kartika Candra (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
This study aims to determine the influence of consumer attitude and motivation on purchase intention at the Rasqya grocery MSME in Sambinae Subdistrict, Bima City. The research problem arises from the importance of understanding consumer psychological factors in enhancing purchasing power, particularly in the micro, small, and medium enterprise sector. The research method used is a quantitative approach, with data collected through questionnaires distributed to consumers of the MSME. Data analysis was conducted using multiple linear regression to test the influence of independent variables on the dependent variable. The results indicate that consumer attitude and motivation simultaneously have a significant effect on purchase intention. Partially, motivation has a more dominant influence than consumer attitude. These findings highlight the importance of strategies that enhance consumer motivation, such as promotions and customer service, to encourage purchasing decisions.